2014
DOI: 10.1111/bjdp.12062
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structure of the ‘ToM Storybooks’: A test evaluating multiple components of Theory of Mind

Abstract: This study examined the factorial structure of the Theory of Mind (ToM) Storybooks, a comprehensive 93-item instrument tapping the five components in Wellman's model of ToM (emotion recognition, understanding of desire and beliefs, ability to distinguish between physical and mental entities, and awareness of the link between perception and knowledge). A sample of 681 three- to eight-year-old Italian children was divided into three age groups to assess whether factorial structure varied across different age ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The internal consistency [Cronbach’s alphas: ToM total score = 0.95, ToM sub-score 1 (emotion recognition) = 0.83, ToM sub-score 2 (physical/mental) = 0.88, ToM sub-score 3 (seeing knowing) = 0.51, ToM sub-score 4 (desires) = 0.84, ToM sub-score 5 (beliefs) = 0.89], test-retest reliability ( r = 0.86, p = 0.001 for typically developing children, r = 0.98 for children with PDD–NOS), inter-rater reliability (Cohen’s Kappa = 0.81–0.97), divergent and convergent validity are good (see also Blijd-Hoogewys et al, 2008, 2010). The ToM Storybooks has been translated in different languages, such as English, Finnish, French, Italian, and Spanish; and it has been standardized on two European populations, namely Dutch children (Blijd-Hoogewys et al, 2008) and Italian children (Molina and Bulgarelli, 2012; Bulgarelli et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency [Cronbach’s alphas: ToM total score = 0.95, ToM sub-score 1 (emotion recognition) = 0.83, ToM sub-score 2 (physical/mental) = 0.88, ToM sub-score 3 (seeing knowing) = 0.51, ToM sub-score 4 (desires) = 0.84, ToM sub-score 5 (beliefs) = 0.89], test-retest reliability ( r = 0.86, p = 0.001 for typically developing children, r = 0.98 for children with PDD–NOS), inter-rater reliability (Cohen’s Kappa = 0.81–0.97), divergent and convergent validity are good (see also Blijd-Hoogewys et al, 2008, 2010). The ToM Storybooks has been translated in different languages, such as English, Finnish, French, Italian, and Spanish; and it has been standardized on two European populations, namely Dutch children (Blijd-Hoogewys et al, 2008) and Italian children (Molina and Bulgarelli, 2012; Bulgarelli et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…At three separate sessions conducted within a month of each other, the children were individually assessed at kindergarten using four standardized tests: the ToM Storybooks (Molina and Bulgarelli, 2012a; Bulgarelli et al, 2015) were used to assess ToM and the Test of Emotion Comprehension (TEC, Pons and Harris, 2000; Albanese and Molina, 2013) to assess EU; the Leiter-R (Roid and Miller, 2002; US version: 1997) was used to assess non-verbal IQ; the Peabody Picture Vocabulary Test (Dunn and Dunn, 1981), in its Italian version (Stella et al, 2000) was used to assess receptive language, reported as Verbal Quotient (VQ).…”
Section: Methodsmentioning
confidence: 99%
“…Mental state talk is the set of terms used by people to attribute physiological (e.g., being hungry), perceptual (e.g., see), willing (e.g., desire), emotional (e.g., anger), cognitive (e.g., knowing), moral (e.g., judge), and socio‐relational (e.g., helping) state to others (Bretherton & Beegley, ; Bulgarelli, Testa, & Molina, ; Symons, ). MST is a reliable measure of children's ToM, as demonstrated by the significant correlation with standardized measures of ToM (Accorti Gamannossi & Pinto, ; Peterson & Slaughter, ).…”
Section: Introductionmentioning
confidence: 99%